Methodical instructions for conducting practical classes in the discipline "Providing innovations" - Zaruba, Viktor (Національний технічний університет "Харківський політехнічний інститут", 2025)
Applicants receive Methodical recommendations for practical classes in the discipline "Providing innovations" at the beginning of the academic semester. Before the beginning of each practical session, applicants must familiarize themselves with the content of the tasks that will be solved in it, and with the methods (algorithms) of their solution. During practical classes in the teaching of the discipline "Providing innovations", the use of such educational technologies as mini-lectures and work in small groups is provided. Mini-lectures involve the presentation of educational material in a short period of time, are characterized by a significant capacity and are usually conducted as part of practical classes. According to their type, depending on the didactic purpose and place in the logical structure of the educational material, mini-lectures can be review or instructional lectures. The review lecture is held with the aim of updating the knowledge of the students, which they have already acquired before and related to the topic of one or more practical classes. An important point of the review lecture is the selection and structuring of educational material, which ensures the preparation of students for a logical and systematic understanding of the purpose and tasks of each practical lesson. The lecture-instruction immediately precedes the performance of the practical session and is held in order to prepare the applicants for its performance, reveals the content and sequence of the tasks, theoretical and applied aspects of its results. While working in small groups, students are invited to form groups of 5-6 people and present their vision and perception of the material at the end of the class. Work in small groups should create opportunities for the participation of each student in the work on the topic of the lesson, ensure the formation of personal qualities and communication experience. The teaching and methodical materials for conducting practical classes, which are given here, are grouped into 2 sections that correspond to the complex topics specified in the syllabus of the discipline "Providing innovations": Calculations of economic efficiency assessment indicators of innovative projects, Application of econometric models to establish competitive prices for new products. Each complex topic consists of educational and methodical materials for conducting mini-lectures and individual practical classes. Complex topics consist of topics of separate practical classes.
Keywords: methodical instructions; practical classes; providing innovations; marketing; economic efficiency; innovative projects